Stabilitas Digester Anaerobik Satu Tahap dalam Produksi Biogas pada Variasi Temperatur Menggunakan Reaktor Batch - Trisakti, Bambang; Irvan; Sitompul, Desi Berliana (Talenta Publisher (Universitas Sumatera Utara), 2021)
Anaerobic digestion is the decomposition of organic matter by microbes into methane, carbon dioxide, and hydrogen sulfide in the absence of oxygen. This study aimed to obtain the stability of the one stage anaerobic digester in biogas production that was seen through pH and alkalinity parameters. The process was carried out by varying the temperature, which is 35 °C, 45 °C, and 55 °C with pH maintained 7 (± 0.2). Analysis of pH and alkalinity was carried out to assess the stability of reactor using samples taken from the reactor overflow. The pH profile produced was relatively stable with a pH range between 6.8 - 7.3. The resulting alkalinity is relatively stable with aalkalinity range between 3.500 – 4.500 mg/L. The volume of biogas produced at 35 °C, 45 °C, and 55 °C respectively are 2065 mL, 3830 mL, and 4570 mL with the highest concentrations of methane (CH4), Carbon dioxide (CO2) and trace Hydrogen Sulfide (H2S) at a temperature of 55 oC obtained the value of the composition of methane, carbon dioxide, and hydrogen sulfide each at 89,000 %, 11,000 %, and 0,011 %.